Nomogram for prediction of prognosis in patients with initially unresectable colorectal liver metastases. Issue 5 (18th January 2016) - Imai, K.; Allard, M.‐A.; Castro Benitez, C.; Vibert, E.; Sa Cunha, A.; Cherqui, D.; Castaing, D.; Bismuth, H.; Baba, H.; Adam, R.
Abstract : Background: Although recent advances in surgery and chemotherapy have increasingly enabled hepatectomy in patients with initially unresectable colorectal liver metastases (CRLM), not all such patients benefit from surgery. The aim of this study was to develop a nomogram to predict survival after hepatectomy for initially unresectable CRLM. Methods: Patients with initially unresectable CRLM treated with chemotherapy followed by hepatectomy between 1990 and 2012 were included in the study. A nomogram to predict survival was developed based on a multivariable Cox model. The predictive performance of the model was assessed according to the C‐statistic, Kaplan–Meier curve and calibration plots. Results: Of a total of 439 patients, liver and globally completed surgery was achieved in 380 (86·6 per cent) and 335 (76·3 per cent) patients respectively. The 5‐year overall and disease‐free survival rates were 39·9 and 10·0 per cent respectively. Based on the Cox model, the following five factors were selected for the nomogram and assigned specific scores: node‐positive primary, 5; more than six metastases at hepatectomy, 7; carbohydrate antigen 19–9 level at hepatectomy above 37 units/ml, 10; disease progression during first‐line chemotherapy, 9; and presence of extrahepatic disease, 4. The model achieved relatively good discrimination and calibration, with a C‐statistic of 0·66. The overall survival rate for patients with a score greater than 16 was significantly worse than that for patients with a score of 16 or less (5‐year survival rate 4 versus 46·3 per cent respectively; P < 0·001). Conclusion: The nomogram facilitates personalized assessment of prognosis for patients with initially unresectable CRLM treated with chemotherapy and with planned resection. Abstract : Useful clinical scoring system